2021
DOI: 10.3390/s21041497
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Density Structure of the Jiuzhaigou Ms7.0 Earthquake Area Revealed by the Barkam–Jiuzhaigou–Wuqi Gravity Profile

Abstract: The Barkam–Jiuzhaigou–Wuqi gravity profile extends across the Jiuzhaigou Ms7.0 earthquake (in 2017) zone and passes through several historical big earthquakes’ zones. We have obtained Bouguer gravity anomalies along the profile composed of 365 gravity observation stations with Global Positioning System (GPS) coordinates, analyzed the observed data and inverted subsurface density structure. The results show that the Moho depth has a big lateral variation from southwest to northeast, which shallows from 57 km to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A study using GRACE satellite data revealed large-scale gravity and mass changes throughout three tectonic plates and connected slabs prior to the occurrence of the 2011 Tohoku Oki Mw9.0 earthquake [ 12 ]. In previous studies on the Tibetan Plateau, high-accuracy absolute and relative gravity measurements were used to detect anomalies [ 13 , 14 , 15 , 16 , 17 ]. Before the occurrence of the 2015 Nepal Mw7.8 earthquake, a gravitational increase of up to 22.40 ± 1.11 μGal/yr was observed at four absolute gravity stations surveyed during 2010/2011–2013, and the modeled source region of the gravity field was found be consistent with the opinion that some of the southern Tibetan Plateau crust was involved in storing the strain energy that drove the Nepal earthquake [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study using GRACE satellite data revealed large-scale gravity and mass changes throughout three tectonic plates and connected slabs prior to the occurrence of the 2011 Tohoku Oki Mw9.0 earthquake [ 12 ]. In previous studies on the Tibetan Plateau, high-accuracy absolute and relative gravity measurements were used to detect anomalies [ 13 , 14 , 15 , 16 , 17 ]. Before the occurrence of the 2015 Nepal Mw7.8 earthquake, a gravitational increase of up to 22.40 ± 1.11 μGal/yr was observed at four absolute gravity stations surveyed during 2010/2011–2013, and the modeled source region of the gravity field was found be consistent with the opinion that some of the southern Tibetan Plateau crust was involved in storing the strain energy that drove the Nepal earthquake [ 13 ].…”
Section: Introductionmentioning
confidence: 99%